Petrogenesis of the Late Oligocene Takht batholith, Southeastern Iran: Implications for the Diachronous Nature of the Arabia–Eurasia Collision - Pang, Kwan-Nang; Fazlnia, Abdolnaser; Ji, Wei-Qiang; Jamei, Susan; Jafari, Amin (Frontiers in Earth Science, 2020)
Zircon U-Pb age, mineral compositional, elemental and Sr-Nd isotopic data are documented for intermediate to felsic rocks in the Takht batholith, a Late Oligocene igneous complex in the southeastern segment of the Urumieh-Dokhtar belt, Iran, to investigate magma genesis in the context of regional tectonics. A large part of the magmatic belt formed by northward subduction of the Neotethys before the Arabia–Eurasia continental collision. Zircon U-Pb age data indicate the batholith crystallized at ∼25 Ma, an age consistent with previous results. Geochemical data indicate that the rocks share features typical of calc-alkaline magmas and I-type granitoids. The least evolved magma inferred from the data has basaltic andesite composition, consistent with either of the following origins: (i) a partial melt of the mantle followed by differentiation, or (ii) a partial melt of the lower crust. With increasing SiO2, (87Sr/86Sr)25Ma increases from 0.7053 to 0.7073, and εNd25Ma decreases from −0.3 to −2.9, consistent with increasing effects of assimilation–fractional crystallization, although processes such as magma mixing and melting of heterogeneous source rocks cannot be entirely ruled out. Aluminum-in-hornblende thermometry indicates that the batholith might have emplaced at ∼6.5 km or shallower paleo-depths. Moho depth proxies Sr/Y and (La/Yb)N yield crustal thickness of ∼20–30 km, showing no evidence for magma processing within thick crust. Overall, our results indicate that the Takht batholith is a Cordilleran-type batholith formed beneath a continental or transitional arc of normal crustal thickness. This is consistent with the notion that Arabia and Eurasia have collided in a diachronous manner, propagating from the northwest to the southeast since the Late Eocene–Early Oligocene.